2011
DOI: 10.1021/es2010368
|View full text |Cite
|
Sign up to set email alerts
|

Strontium and Cesium Release Mechanisms during Unsaturated Flow through Waste-Weathered Hanford Sediments

Abstract: TitleStrontium and cesium release mechanisms during unsaturated flow through wasteweathered Hanford sediments Cs. The mineral composition of the weathered sediments showed that zeolite (chabazite-type) and feldspathoid (sodalitetype) were the major byproducts but different contents depending on the weathering conditions.Reactive transport modeling indicated that Cs leaching was controlled by ion-exchange, while Sr release was affected primarily by dissolution of the secondary minerals. The later release of K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…In this regard, experimental studies explored clay alteration and formation of new phases with different swelling and adsorption properties under conditions expected to occur within a Nuclear Waste repository or in the subsurface of the Hanford site. In the latter location, highly alkaline waste solutions leached from storage tanks are now in contact with clay-bearing sediments in the subsurface (Chorover et al, 2003(Chorover et al, , 2008Zhao et al, 2004;Choi et al, 2005a,b;Crosson et al, 2006;Chang et al, 2011;Perdrial et al, 2011). In a potential Nuclear Waste repository with a multi-barrier system of bentonite buffers, steel canisters and concrete overpacks, alkaline pore waters may also form through dissolution of the concrete and oxidation of metallic Fe.…”
Section: Products Of Clay Alteration and Their Interaction With Contamentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, experimental studies explored clay alteration and formation of new phases with different swelling and adsorption properties under conditions expected to occur within a Nuclear Waste repository or in the subsurface of the Hanford site. In the latter location, highly alkaline waste solutions leached from storage tanks are now in contact with clay-bearing sediments in the subsurface (Chorover et al, 2003(Chorover et al, , 2008Zhao et al, 2004;Choi et al, 2005a,b;Crosson et al, 2006;Chang et al, 2011;Perdrial et al, 2011). In a potential Nuclear Waste repository with a multi-barrier system of bentonite buffers, steel canisters and concrete overpacks, alkaline pore waters may also form through dissolution of the concrete and oxidation of metallic Fe.…”
Section: Products Of Clay Alteration and Their Interaction With Contamentioning
confidence: 99%
“…Studies simulating the interaction of Hanford tank waste solution with clay minerals (Na-Al-NO 3 -system with pH values P12) identified for example illite, the feldspathoids cancrinite, sodalite and the zeolites chabazite and X as alteration products of kaolinite, illite, vermiculite and montmorillonite (Chorover et al, 2003;Zhao et al, 2004;Crosson et al, 2006;Chang et al, 2011). Studies further indicated enhanced uptake and incorporation of Sr, Cs and I (representing the radionuclides 90 Sr, 137 Cs and 129 I) by feldspathoids and zeolites relative to the unaltered clays (Chorover et al, 2003(Chorover et al, , 2008Choi et al, 2005a,b;Perdrial et al, 2011).…”
Section: Products Of Clay Alteration and Their Interaction With Contamentioning
confidence: 99%
“…The source solution was pumped through the columns using a peristaltic pump (Ismatec 78001-02) at desired flow rates (1 mL/min for column 1 and most of time for column 2 and 1.85 mL/min between day 26 to day 27 for phase II of column 2) ( Table 2). In phase III of column 2, the source solution was switched from the Ca-citrate-phosphate solution to the uncontaminated groundwater (Table 3), obtained from the same site where the sediment was collected, after spiked with 1 mg/L Sr (stable Sr as a surrogate for Sr-90 (Rabideau et al, 2005;Chang et al, 2011)) ( Table 2). All source solutions were supplied to the columns as continuous injection systems.…”
Section: Source Solutionsmentioning
confidence: 99%
“…Contact of the released hyperalkaline tank fluid with the underlying sediments has caused geochemical changes, resulting in primary mineral dissolution and precipitation of secondary minerals (Bickmore et al, 2001;Chorover et al, 2003Chorover et al, , 2008Qafoku et al, 2003;Mashal et al, 2004;Zhao et al, 2004;Deng et al, 2006a,b;Rod et al, 2010;Chang et al, 2011). The caustic tank leachate dissolves silicate minerals and the released Si can react with Al, Na, and anions such as NO À 3 ; CO 2À 3 , or OH À from tank wastes to form secondary mineral precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, crystalline feldspathoids such as sodalite and cancrinite [Na 8 Si 6 Al 6 O 24 (NO 3 ) 2 ] can be formed at temperatures above 40°C and at high NaOH (>1 M) solutions (Bickmore et al, 2001;Mattigod et al, 2002;Qafoku et al, 2003;Mashal et al, 2004;Deng et al, 2006a). Compared to the primary minerals, these neo-formed secondary minerals demonstrate elevated sorption capacity resulting from increased surface adsorption and co-precipitation of radionuclides such as Sr and Cs (Chorover et al, 2003;Mon et al, 2005;Um et al, 2005;Choi et al, 2006;Rod et al, 2010;Chang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%